Exploring the Potential of Virtual Reality in Eating Disorder Treatment - Weronika Barbara Grywińska; Aleksandra Okońska; Julia Kozakiewicz; Kamil Kościelecki; Agnieszka Kalisz; Iwona Skorulska; Klaudia Mączewska; Patrycja Długozima; Paulina Grzeszczuk; Aleksandra Głowacka (Quality in Sport)
Abstract